1991
DOI: 10.1017/s1047951100010349
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cardiovascular malformations: The state of the art

Abstract: SummaryA historical review highlights an interest in the etiology of birth defects over the course of several centuries and recalls specific hypotheses on the origin of cardiovascular defects postulated 60 years ago. The “State of the Art” of the epidemiology of cardiovascular malformations is characterized by an expanding base of knowledge which holds promise for eventual preventive interventions. Epidemiologic investigations conducted in the past decade have led to an increased understanding of the benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…The rates of specific cardiac defects in our study are generally comparable with 186 those reported from the Baltimore-Washington study by Ferencz et al and from EUROCAT registry [1,6,7]. As 187 expected, the most frequent diagnosis was ventricular septal defect, followed by atrial septal defect, patent 188 arterial duct, pulmonary stenosis, and atrioventricular septal defects.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The rates of specific cardiac defects in our study are generally comparable with 186 those reported from the Baltimore-Washington study by Ferencz et al and from EUROCAT registry [1,6,7]. As 187 expected, the most frequent diagnosis was ventricular septal defect, followed by atrial septal defect, patent 188 arterial duct, pulmonary stenosis, and atrioventricular septal defects.…”
supporting
confidence: 85%
“…On the other hand, the number of 44 adults with some form of congenital heart disease is growing rapidly as therapy becomes increasingly effective 45 [23]. Quantification of birth prevalence and spectrum of malformations, along with analysis of past trends of 46 management, allow for future planning of health services [7]. Congenital cardiac malformations are frequently associated with other non-cardiac congenital malformations and chromosomal anomalies.…”
mentioning
confidence: 99%
“…Approximately 25-40% of CHDs are ventricular septal defects (VSDs), making VSD the most common type of CHD (Ferencz and Correa Villasenor, 1991;Tikkanen and Heinonen, 1991;Botto et al, 2001;Hoffman and Kaplan, 2002). Children with VSD are at risk for endocarditis, pulmonary infection, ventricular arrhythmias, and death from heart failure or pulmonary hypertension Ferencz et al, 1997;Brickner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In most patients, CHD occurs as an isolated malformation, but about 33% have associated anomalies [4]. The reported incidence of associated extracardiac anomalies ranges from 7% to 45% [3,7]. This wide variation between reports on prevalence and incidence of associated malformations is the result of different methodologies used in various studies, as well as variations in ethnic occurrence and regional differences.…”
Section: Introductionmentioning
confidence: 99%